UPAYA MENINGKATKAN MEMBACA PEMAHAMAN MELALUI MODEL PEMBELAJARAN KOOPERATIF LEARNING STARTS WITH A QUESTION PADA SISWA KELAS IV SD NEGERI 7 SEKAYU KABUPATEN MUSI BANYUASIN - Reni Marlina (Universitas PGRI Palembang, 2017)
Abstract: This study was conducted to describe the problem in this research is how efforts to improve reading comprehension through the use of cooperative learning model learnig start with a question on the fourth grade students of SD Negeri 7 Sekayu Musi Banyuasin. Solving the problem in this study is a cooperative learning model learnig start with a question that can lead students to be more active and focused on the subject matter provided through discussions that are conducted under the direction and guidance of teachers so that students are more quickly understand the subject matter and not easily saturated with activity learning. An increase in the students 'learning activities 60.00 in cycle 1 increased by 13.02 thus be 73.02 in cycle 2 and increase again 18.41 into 91.43 in cycle 3 students' reading comprehension ability of the average value of the initial test (pretest), namely 62.86 in the initial test (pretest) to 69.86 on the test cycle 1 with a percentage increase of 11.14%, increased again to 74.86 in cycle 2 with a percentage increase of 19.09, and increased again be 84.29 on the test cycle 3 with a percentage increase of 34.09%. Therefore, based on the results of the implementation of the PTK, the initial test (pretest), the first cycle, and secondly it can be concluded that the use of the learning model learning starts with a questio can improve the quality of learning both student learning activities and reading comprehension in the fourth grade students of SD Negeri 7 Sekayu District Banyuasin.